Validitas dan Praktikalitas Lembar Kerja Siswa Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SD/MI - bonita irani; Melly Andriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aimed at developing student workbook Problem Based Learning model based that was valid and practical to increase student mathematic problem-solving ability. This research was instigated by student mathematic problem-solving ability that was on low category, student workbook that was inappropriate to increase student mathematic problem-solving ability. It was a Research and Development with 4-D (Define, Design, Develop, Disseminate) model. The subjects of this research were 39 students of the fifth grade of class C, and the object was mathematics student workbook Problem Based Learning model based. The collected data were primary, and the techniques of collecting the data were interview, questionnaire, test, and documentation. The instruments of collecting the data were the instruments of validity test, practicality test, pretest and posttest questions of mathematic problem-solving ability. The obtained data were analyzed by using Descriptive qualitative and descriptive quantitative analysis techniques. Based on the research findings and data analyses, it could be concluded that validity level of student workbook was valid with 86.92% percentage, and it had been proper to be tested. After testing, the practicality level was on very practical category with 95.6% percentage. The analysis result of student mathematic problem-solving ability level after using the workbook generally was on high category with 83.06% percentage. It meant that students were able to solve the problems overall.